2010
DOI: 10.1097/bpo.0b013e3181cfcd2e
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Osteochondritis Dissecans of the Knee: Perifocal Sclerotic Rim as a Prognostic Factor of Healing

Abstract: Prognostic study, Level II (retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…27 The radiodensity of the rim of the parent bone adjacent to the OCD lesion was considered a measure of sclerosis in our study and demonstrated only fair to moderate reliability. Reliability may be improved by clarifying the question from ''what is the radiodensity of the rim of the parent bone'' to the more straightforward question of ''what is the sclerotic rim density.''…”
Section: Discussionmentioning
confidence: 99%
“…27 The radiodensity of the rim of the parent bone adjacent to the OCD lesion was considered a measure of sclerosis in our study and demonstrated only fair to moderate reliability. Reliability may be improved by clarifying the question from ''what is the radiodensity of the rim of the parent bone'' to the more straightforward question of ''what is the sclerotic rim density.''…”
Section: Discussionmentioning
confidence: 99%
“…Initial treatment is with immobilization of the joint, with or without fixation or excision or large displaced fragments. Arthroscopy will allow direct visualization of the fragment, testing of stability and fixation, drilling or excision [44][45][46][47]. The long-term outcome is variable, but may, rarely, precipitate the end of competitive sport.…”
Section: Osteochondritis Dissecans (Ocd)mentioning
confidence: 99%
“…From these, assessment of size and stability will help guide management. Perifocal sclerosis is a negative prognostic indicator [45]. Initial treatment is with immobilization of the joint, with or without fixation or excision or large displaced fragments.…”
Section: Osteochondritis Dissecans (Ocd)mentioning
confidence: 99%
“…Ramirez et al, in a recent review of eightyfive children and adolescents, demonstrated that the presence of a sclerotic rim around the lesion and older age correlated with a lower rate of spontaneous healing 23 . Fixation techniques used for stabilization of unstable juvenile osteochondritis dissecans lesions vary.…”
Section: Sports Medicinementioning
confidence: 99%